Antibiotic susceptibility patterns of pathogenic bacteria isolated from the operating room of the Al Sader Teaching Hospital (Iraq) - B. Aljaryan, Hajir; Khalil Al-Shamari, Ataa; Ahmed Nayyef, Ali; Al-Ameedy, Taif Hussein; Rabeea, Haneen; Ali, Fatimatulzahraa (Pharmakeftiki, 2025)
In hospital settings, microbial contamination plays a major role in the transmission of healthcare-associated illnesses. This study aimed at evaluating the level of bacterial contamination in operating rooms. A cross-sectional study was carried out in the operating theatres and delivery rooms of Al Sader Teaching Hospital in Iraq, between July and November 2023. Samples were collected and sent to the laboratory for standard diagnostic analysis and the undertaking of antimicrobial sensitivity testing. The analysis revealed varying contamination rates across different operating rooms. The most frequently detected bacterial isolates belonged to Escherichia coli (12%), Klebsiella pneumoniae (17%), Pseudomonas aeruginosa (20%), and Staphylococcus aureus (25%). The antibiotic sensitivity testing showed that different bacterial strains exhibited varied responses to antibiotics, underscoring the challenges in treating infections caused by these pathogens. These findings highlight the importance of monitoring antibiotic resistance patterns in these bacterial strains in order to guide treatment decisions and enhance patient outcomes.